2015
DOI: 10.1038/nrneurol.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Statins, cognition, and dementia—systematic review and methodological commentary

Abstract: Firm conclusions about whether mid-life or long-term statin use has an impact on cognitive decline and dementia remain elusive. Here, our objective was to systematically review, synthesize and critique the epidemiological literature that examines the relationship between statin use and cognition, so as to assess the current state of knowledge, identify gaps in our understanding, and make recommendations for future research. We summarize the findings of randomized controlled trials (RCTs) and observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 94 publications
0
110
2
3
Order By: Relevance
“…All participants were required to be taking a statin medication. This inclusion criterion was implemented in order to standardize the study population, as statins are the standard of care in CAD and may impact sphingolipid concentrations (Ng et al., 2014; Wei et al., 2013) as well as mood and cognition (Kim et al., 2015; Power, Weuve, Sharrett, Blacker, & Gottesman, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…All participants were required to be taking a statin medication. This inclusion criterion was implemented in order to standardize the study population, as statins are the standard of care in CAD and may impact sphingolipid concentrations (Ng et al., 2014; Wei et al., 2013) as well as mood and cognition (Kim et al., 2015; Power, Weuve, Sharrett, Blacker, & Gottesman, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the association between good LDL control and cognitive impairment during follow-up in SAMMPRIS is more difficult to explain. While a few studies have suggested that lipid-lowering medication use may be linked to memory loss [23,24], an alternative explanation is that cholesterol levels decrease with age, chronic disease, poor nutrition, and inflammation, so perhaps the association between low LDL and cognitive impairment during follow-up is confounded by baseline older age or lower weight, which were associated with cognitive impairment in this study, or even related to another unmeasured factor. Another possibility for the paradoxical association between low LDL and cognitive impairment is that the result may be affected by index-event bias [25] because this analysis was focused on a different outcome (cognitive impairment) than the cohort was selected for in SAMMPRIS (stroke or TIA due to severe ICAS).…”
Section: Discussionmentioning
confidence: 53%
“…However, clinical studies of statins in aging and dementia have yielded only tenuous conclusions, with some observational data suggesting a protective association but other observational studies and randomized controlled trials not supporting this [6, 7]. In addition, existing studies using in vivo neuroimaging and postmortem neuropathology as outcomes have yielded conflicting results and have been limited by modest sample sizes and lack of generalizability [811].…”
Section: Introductionmentioning
confidence: 99%